Mathematics as a cultural system - Wilder, Raymond Louis, 1896-1982 (Foundations & philosophy of science & technology., 1981)
Mathematics as a Cultural System discusses the relationship between mathematics and culture. The book is comprised of eight chapters discussing topics that support the concept of mathematics as a cultural system.